Optimasi Sistem Pencahayaan Buatan pada Budget Hotel di Surabaya - Steffi Julia Soegandhi; Hedy Constancia Indrani; purnama esa dora tedjokoesomo (Intra, 2015)
Budget hotel is a kind of hotel favored by people as place to stay temporarily with affordable cost. The low cost at budget hotel causes the lack of attention on the lighting system, especially the main product of a hotel, that is the bedroom. This research aims to analyze and to provide solution to an optimum lighting design on budget hotel in Surabaya, that is Hotel 88 and Hotel Bekizaar. Optimization is done by using the software DIALux 4.10. Analysis result shows that all lighting conditionsin both hotel has not met SNI standard, therefore it needs some customizations to optimize the lighting level by altering the type, position, quantity, and color of the artificial lighting.